Climate change and the agricultural history of a mid-elevation Andean montane forest. (September 2015) - Bush, Mark B; Mosblech, Nicole A Sublette; Church, Warren
The steep, wet, forested, slopes of the mid-elevation Andes have often been dismissed as inimical to human occupation. A lack of ancient lakes in these habitats has limited the availability of paleoecologists to contribute to this discussion. Here, we present fossil pollen and charcoal data from Lake Pomacochas in northern Peru, which is a 70-m-deep lake lying at 2100 m a.s.l. We present a c. 3500-year history of both significant climate change and site occupancy by humans. Maize pollen is present in sediments throughout much of this record, though there are times when its cultivation is either abandoned, or moves back from the shoreline, for example, between c. 3500 and 2700 cal. yr BP and post 1200 cal. yr BP. By comparing our record with isotopic data derived from cave calcite we are able to show that dry times favored maize cultivation in this setting. In the last 1200 years, large-scale social changes in the Andes, such as the emergence of the Chachapoya culture and the invasion of Europeans, appear to be reflected in the fossil pollen and charcoal record.